2004
DOI: 10.1291/hypres.27.31
|View full text |Cite
|
Sign up to set email alerts
|

Association between Hypertension and the .ALPHA.-Adducin, .BETA.1-Adrenoreceptor, and G-Protein .BETA.3 Subunit Genes in the Japanese Population; the Suita Study

Abstract: eases, and a single study even employing 1,880 subjects may lack the statistical power to detect a real association. Accordingly, it will be necessary to verify the association between these three genes and hypertension using a larger number of subjects from the Suita cohort or another population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
2
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 27 publications
4
40
2
3
Order By: Relevance
“…Results from studies on Japanese subjects are contradictory, in which three studies showed a positive association with hypertension 1 0 and three studies a negative association. [22][23][24][25][26] As we have shown that diastolic blood pressure is significantly lower in TT homozygotes than in CC homozygotes in the subjects from general health examinations, while the TT, CT, and CC carriers show the same frequencies of hypertension in the subjects with diabetes, we may therefore not associate this polymorphism with hypertension.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Results from studies on Japanese subjects are contradictory, in which three studies showed a positive association with hypertension 1 0 and three studies a negative association. [22][23][24][25][26] As we have shown that diastolic blood pressure is significantly lower in TT homozygotes than in CC homozygotes in the subjects from general health examinations, while the TT, CT, and CC carriers show the same frequencies of hypertension in the subjects with diabetes, we may therefore not associate this polymorphism with hypertension.…”
Section: Discussionmentioning
confidence: 80%
“…Almost the same frequency as previously reported in Japanese subjects (0.46 -0.59). 4,[22][23][24][25][26][27][28] The frequency varies to some extent among other races: in America Indians, 0.11 -0.33; in Caucasians, 0.21 -0.38; in Mongolians 0.42 -0.52; and in black Africans, 0.65 -0.91. 3 G protein activation is enhanced in immortalized lymphoblasts from German patients with essential hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of single nucleotide polymorphisms (SNPs) of β ADR subtypes have recently been reported to be positional candidate genes for cardiovascular diseases ( 12 , 13 ). For instance, the genotype of the Arg389Gly polymorphism in the human β 1 -adrenoceptor ( β 1 ADR) gene is reported to be associated with acute myocardial infarction ( 14 ) and hypertensive status ( 15 ), an association study ( 16 ) suggested that the gene encoding the β 2 -adrenoceptor ( β 2 ADR) was associated with essential hypertension; and the Arg64 allele of the β 3 -adrenoceptor ( β 3 ADR) gene is associated with obesity-related phenotypes ( 17 ), insulin resistance, hypertension, coronary artery disease and earlier age of onset of diabetes ( 18 ). The essential effects of the three β ADRs, however, need to be further clarified.…”
Section: Introductionmentioning
confidence: 99%